Concerted Cultivation Among Low-Income Black and Latino Families - Sonnenschein, Susan; Metzger, Shari R.; Gay, Brittany (Springer Nature Switzerland AG., 2018)
This chapter examines low-income Black and Latino parents’ beliefs and practices about providing an educationally rich environment for their children. More specifically, it focuses on what parents believe about how their preschool children learn, their role in such learning, and the reading and math activities they make available to their children. Using a mixed-methods approach, we found that both Black and Latino parents expressed beliefs consistent with Lareau’s (2003) notion of concerted cultivation by engaging in educational activities with their children and purposefully providing educational materials for them. In addition, there were no significant differences between Black and Latino parents in the approaches they chose to foster their children’s reading and math skills. Future research can utilize the findings from this study to help promote the academic success of low-income children by building upon the beliefs of Black and Latino parents and the activities that they endorse.
Keywords: concerted cultivation; academic socialization; low-income parents; preschool children; reading; math